Platelet aggregation pattern on light transmission aggregometry among Malaysian healthy individuals - Muhsin, Azlina; Mohd Tohit, Eusni Rahayu; Md Noor, Sabariah; Abdul Karim, Faraizah (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2020)
Introduction: Platelet aggregation test using light transmission aggregometry (LTA) is considered as the gold standard for evaluation of platelet function. Variations of platelet aggregation had been reported in apparently healthy individuals whereby a normal cut–off value established locally is highly recommended. This study aims to determine the platelet aggregation pattern and the preliminary findings on reference values for multiple agonists–induced platelet aggregation among Malaysian healthy individuals in a single centre. Method: A total number of 63 informed consented healthy individuals consisted of Malay, Chinese and Indian were recruited among staff and blood donors at National Blood Centre, Kuala Lumpur. Platelet aggregation was measured using LTA against adenosine diphosphate 10 µM (ADP10), collagen 0.19 mg/mL (COL), ristocetin 1.5 mg/mL (RIS), arachidonic acid 1 mM (AA) and epinephrine 10 µM (EPI). Results were expressed as percent final aggregation (%FA). Reference values were calculated from mean±2SD. Results: Age, gender and ethnic groups had no significant effect on platelet aggregation. A variability of platelet aggregation response to EPI was observed among the healthy individuals. Ten of 33 respondents (30%) had impaired aggregation with <20% FA in response to EPI. The local population showed a slightly higher aggregation pattern in response to COL, RIS, AA and EPI (excluding non-responders) compared to manufacturer’s reference values. Conclusion: This study has provided a glimpse of the aggregation pattern of the local nationality showing considerable differences in the reference values from manufacturer’s; thus highlighting the need of establishing local reference values.